2019
DOI: 10.1096/fj.201901358rr
|View full text |Cite
|
Sign up to set email alerts
|

The vicious cycle between transglutaminase 2 and reactive oxygen species in hyperglycemic memory–induced endothelial dysfunction

Abstract: Clinical trials suggested that the vascular system can remember episodes of poor glycemic control through a phenomenon known as hyperglycemic memory (HGM). HGM is associated with long‐term diabetic vascular complications in type 1 and type 2 diabetes, although the molecular mechanism of that association is not clearly understood. We hypothesized that transglutaminase 2 (TGase2) and intracellular reactive oxygen species (ROS) play a key role in HGM‐induced vascular dysfunction. We found that hyperglycemia induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 40 publications
0
46
0
Order By: Relevance
“…Hyperglycemia increases the intracellular NADH/NAD + ratio, increasing the risk of electron leakage from NADH or FADH 2 of the electron transport chain, in turn resulting in increased ROS production (4). Additionally, hyperglycemic states can also decrease the expression and activity of enzymes that eliminate ROS, further aggravating oxidative stress (5). Previous studies have demonstrated that excessive ROS accumulation in the mitochondria induced by hyperglycemia can cause damage to the mitochondrial inner membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia increases the intracellular NADH/NAD + ratio, increasing the risk of electron leakage from NADH or FADH 2 of the electron transport chain, in turn resulting in increased ROS production (4). Additionally, hyperglycemic states can also decrease the expression and activity of enzymes that eliminate ROS, further aggravating oxidative stress (5). Previous studies have demonstrated that excessive ROS accumulation in the mitochondria induced by hyperglycemia can cause damage to the mitochondrial inner membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cell injury and dysfunction are major factors contributed to DVT. Previous studies reported that excessive oxidative stress is a common cause of vascular endothelial cell injury [6][7][8]. Moreover, intracellular reactive oxygen species (ROS) can aggravate apoptosis in vascular endothelial cells and decrease antiapoptotic molecule expression [9].…”
Section: Introductionmentioning
confidence: 99%
“…Appealing theories regarding mechanisms include direct effects of hyperglycemia on fibroblasts to promote their transition to myofibroblasts and subsequent fibrosis; glycation of proteins to form advanced glycation end products (AGEs) that alter the tissue matrices; and increased oxidative stress and inflammation ( Asbun and Villarreal, 2006 ; Ban and Twigg, 2008 ). Studies have demonstrated associations between hyperglycemia ( Skill et al, 2004 ; Bhedi et al, 2020 ), reactive oxygen species ( Lee et al, 2019 ) and inflammatory ( Liu et al, 2019 ) responses and TG2 regulation. Of interest, TG2 -mediated protein serotonylation has been found to be modulated in pancreatic beta cells ( Paulmann et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Highlighting the critical role of TG2 in tissue remodeling, recent studies by Santhanam et al demonstrated that TG2 mediates ventricular ( Oh et al, 2017 ) and aortic ( Steppan et al, 2017 ) contractility, stiffness and function. Furthermore, the events of TG2 alterations are intricately interwoven with influences on transcription factors ( Kumar and Mehta, 2012 ; Brown, 2013 ; Penumatsa et al, 2014 ), inflammation ( Liu et al, 2019 ), oxidative stress ( Lee et al, 2019 ), and fibrogenic signaling ( Olsen et al, 2014 ; Penumatsa et al, 2017 ). Thus, TG2 is a potential target for disruption of tissue stiffness that occurs in diseases of the cardiovascular system and lungs.…”
Section: Introductionmentioning
confidence: 99%